Pengembangan Media Pembelajaran Interaktif pada Mata Pelajaran Jaringan dan Komputer Dasar untuk Kelas X di SMK Negeri 8 Malang menggunakan Metode APPED - I Nyoman Bhayu Kurniawan Putra; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Vocational High School is one unit of formal education in obtaining work expertise in accordance with the desired interest. On the subject of basic computer networks in SMK Negeri 8 Malang the learning process still uses the lecture method with the help of a blackboard and students record explanations from the teacher which results in student grades not meeting the KKM. From the problems obtained, it is necessary to develop interactive learning media using the APPED method. This method has five stages in it, namely analysis and initial research, design, production, evaluation, and dissemination. Results of an ongoing evaluation show that valid media is assessed from three aspects based on a statement from the developer. Alpha testing results show a percentage of 90% with valid categories of material experts, the results of the percentage of media experts amounted to 79.1% with valid categories, and for instructional experts obtained a percentage of 95% with valid categories. The results of beta testing evaluation obtained results of the pretest average of 71 and increased to 88.6 after the post-test was carried out and had fulfilled the KKM. Data normality test produces a significance value of 0.29 for pretest and 0.22 for posttest. The results of the t-test describe the significance values ​​obtained at 0.00. With the significance value obtained <0.05, interactive learning media is effective if used during the learning process.